Kemampuan Kognitif Mahasiswa Pendidikan Bahasa Arab pada Materi Nahwu Berdasarkan Kategori Usia Tahun 2024 - Khoerunisa, Hilda; Tanjung, Henri Peranginangin; Fanirin, Moch. Hasyim (INCARE, International Journal of Educational Resources, 2024)
Students' cognitive abilities play an important role in determining the success of the learning process. In learning Arabic, especially nahwu material, students often have difficulty understanding and applying nahwu concepts. This can occur due to various factors that affect their cognitive abilities, resulting in a lack of in-depth understanding of the material. This study focuses on Arabic Language Education students of Institut Agama Islam Al-Zaytun Indonesia (IAI AL-AZIS) from two age categories (19-24 years and 33-56 years) to find out how their cognitive abilities are in nahwu material through working on questions related to i’râb based on Bloom's taxonomy concept and exploring the factors that affect their cognitive abilities, as well as seeing efforts to develop their cognitive abilities. This study uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, documentation, and tests. The results of the study showed differences in cognitive abilities between students aged 19-24 years and students aged 33-56 years, where younger students have higher abilities in the aspects of remembering, understanding, applying, analyzing, assessing, and creating. However, both age groups showed a higher percentage at the LOTS (lower order thinking skills) level than HOTS (higher order thinking skills). Factors that influence students' cognitive abilities include interest, motivation, mood, anxiety, age, learning methods, learning environment, social support, educational background, and time constraints. Efforts to develop cognitive abilities through social interaction, independence, communication, learning experiences, and responsible attitudes have a positive impact on understanding in both age groups.